Multidrug resistance in Helicobacter pylori infection - Raluca Ioana Dascălu; Alexandra Bolocan; Alexandra Bolocan; Dan Nicolae Păduaru; Dan Nicolae Păduaru; Alexandru Constantinescu; Alexandru Constantinescu; Magda Mihaela Mitache; Anca Daniela Stoica; Anca Daniela Stoica; Octavian Andronic; Octavian Andronic; et al. (Frontiers in Microbiology, 2023)
Helicobacter pylori (Hp), a well-known human pathogen, causes one of the most common chronic bacterial infections and plays an important role in the emergence of chronic progressive gastric inflammation and a variety of gastrointestinal diseases. The prevalence of Hp infection varies worldwide and is indirectly proportional to socio-economic status, especially during childhood. The response to the eradication therapy significantly depends on the antibiotic resistance specific to each geographical region; thus, currently, given the increasing prevalence of antimicrobial resistance (especially to clarithromycin, metronidazole, and levofloxacin), successful treatment for Hp eradication has become a real challenge and a critical issue. The most incriminated factors associated with multidrug resistance (MDR) in Hp proved to be the overuse or the improper use of antibiotics, poor medication adherence, and bacterial-related factors including efflux pumps, mutations, and biofilms. Up to 30% of first-line therapy fails due to poor patient compliance, high gastric acidity, or high bacteremia levels. Hence, it is of great importance to consider new eradication regimens such as vonoprazan-containing triple therapies, quintuple therapies, high-dose dual therapies, and standard triple therapies with probiotics, requiring further studies and thorough assessment. Strain susceptibility testing is also necessary for an optimal approach.